1995
DOI: 10.1002/jcla.1860090211
|View full text |Cite
|
Sign up to set email alerts
|

Acid citrate dextrose (acd) formula a as a new anticoagulant in the measurement of in vitro platelet aggregation

Abstract: To evaluate whether the use of ACD Formula A may affect in vitro platelet function, blood samples were obtained from 21 healthy blood donors and anticoagulated in ACD (acid-citrate dextrose, NIH Formula A), Na citrate 3.8%, and K3EDTA. Platelet count, mean platelet volume, and in vitro platelet aggregation were evaluated on each sample. No significant difference was observed in platelet count and mean platelet volume among the different samples. Conversely, the ACD treated platelets showed a higher reactivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…This finding does not contradict our results from the plasma‐phase platelet count, since the decrease in the plasma‐phase platelet count for the positive control materials could be due to platelet aggregation rather than to surface‐adhered platelets; however, the lack of distinction between surface‐bound platelets on control materials could be due to experimental limitations of the ACP assay for adhered platelet quantification (e.g., inadequate lysing of platelet aggregates). In addition, even though ACD has been commonly used as an anticoagulant for platelet studies for many years and has been shown to be a suitable anticoagulant to characterize platelet aggregation and shear‐induced platelet activation, the calcium‐chelating nature of citrate‐based anticoagulants may suppress platelet adhesion to material surfaces . Evaluation using alternative anticoagulants that can maintain a physiological calcium level will be considered in our future studies.…”
Section: Discussionsupporting
confidence: 93%
“…This finding does not contradict our results from the plasma‐phase platelet count, since the decrease in the plasma‐phase platelet count for the positive control materials could be due to platelet aggregation rather than to surface‐adhered platelets; however, the lack of distinction between surface‐bound platelets on control materials could be due to experimental limitations of the ACP assay for adhered platelet quantification (e.g., inadequate lysing of platelet aggregates). In addition, even though ACD has been commonly used as an anticoagulant for platelet studies for many years and has been shown to be a suitable anticoagulant to characterize platelet aggregation and shear‐induced platelet activation, the calcium‐chelating nature of citrate‐based anticoagulants may suppress platelet adhesion to material surfaces . Evaluation using alternative anticoagulants that can maintain a physiological calcium level will be considered in our future studies.…”
Section: Discussionsupporting
confidence: 93%
“…The previously reported increase of in vitro platelet responsiveness in ACD vs. Na citrate anticoagulated samples at TO was further confirmed. Moreover, as previously demonstrated, the increased reactivity was more evident for the secondary aggregation, while only slight differences were observed upon stimulation of platelets with threshold concentrations of the various agonists (data not shown) (22). Platelet counts and mean platelet volumes were evaluated on ACD and citrated samples at TO and after 6 and 8 hours of storage.…”
Section: R Es U Ltssupporting
confidence: 65%
“…In a previous report we demonstrated that platelets obtained from ACD Formula A anticoagulated blood showed an over-collagen 1 pg/ml, and AA 0.3 mM; the time required to reach the Mx% with the various agonists, the agonist ECsO forADPand EPI-induced aggregation, and the lag phase for collagenand AA-induced aggregation. all reactivity to the agonists higher than citrated samples ( P < 0.001), suggesting the hypothesis that ACD is a more physiological anticoagulant, which is capable of better maintaining the intraplatelet signal transduction mechanisms during P W preparation, thus improving the overall responsiveness of platelets (22). Therefore the present study was designed to evaluate whether the use ofACD FormulaAmay enhance the survival of platelets during storage, thus allowing the continuance of platelet studies over 3 hours.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, ACD-A better maintains the intraplatelet signal transduction mechanisms during PRP preparation, thus improving the overall responsiveness of platelets. 5,6 …”
Section: Methodsmentioning
confidence: 99%